Five‐year outcomes following a randomized trial of femorofemoral and femoropopliteal bypass grafting with heparin‐bonded or standard polytetrafluoroethylene grafts. Issue 10 (1st August 2016) - Lindholt, J. S.; Houlind, K.; Gottschalksen, B.; Pedersen, C. N.; Ravn, H.; Viddal, B.; Pedersen, G.; Rasmussen, M.; Wedel, C.; Bramsen, M. B.
Abstract: Background: Cohort studies suggest superior long‐term patency of luminal heparin‐bonded polytetrafluoroethylene (Hb‐PTFE) bypass grafts compared with standard PTFE grafts. The aim of this study was to compare the outcomes of Hb‐PTFE grafts with those of standard PTFE grafts 5 years after a randomized trial. Methods: Patients with intermittent claudication or critical limb ischaemia requiring femorofemoral or femoropopliteal bypass grafting were randomized in a clinical trial of Hb‐PTFE versus standard PTFE in 11 Scandinavian centres between 2005 and 2009. Patients were followed up for 5 years with clinical assessment and surveillance Duplex ultrasound imaging. The primary endpoint of this study was primary patency. Secondary endpoints included major amputation and mortality. Results: Overall, 569 patients were enrolled in the randomized trial. Some 552 had follow‐up data available for analysis of the primary outcome. Use of Hb‐PTFE significantly improved patency by 37 per cent at 2 years, but 5 years after randomization there was no difference in primary patency (adjusted hazard ratio (HR) 0·95, 95 per cent c.i. 0·71 to 1·28; P = 0·748). In patients with critical limb ischaemia the use of Hb‐PTFE reduced the 5‐year risk of loss of primary patency by 37 per cent (HR 0·63, 0·40 to 0·99; P = 0·049). Conclusion: In this study there was no difference in primary graft patency between Hb‐PTFE and standard PTFE grafts. Patients receiving Hb‐PTFE grafts for critical limb ischaemia were more likely to have a patent graft at 5 years than those with standard PTFE grafts. Abstract : No difference